THE IMPACT OF PERCEIVED VALUE AND FOOD SAFETY CONCERNS ON MALAYSIAN WORKING ADULT POPULATION - Hamid, Junainah Abd; Azam, S.M. Ferdous; shukri, Sakinah mohd (International Journal of Psychosocial Rehabilitation, 2020)
Organic food products are widely used entities in the international market nowadays. The stages of letting aware about the products of food and their advantages instigated the Malaysian working adult population. The major concerns of the people in this regard are food safety issues and their level of understanding the organic food products. The study aimed to analyze effects of food safety concerns and perceived value of working population about advantages of the product of organic food. The examination of this study project would assist the consumers as well as suppliers and retailers in long run to make the better food products to fulfill the needs of population. This could be proved as a huge advantage for the betterment of industry of organic food as well as society.